The Hip - Beydagi, Muharrem Gokhan (Springer International Publishing, 2023)
The hip joint is a ball-and-socket joint surrounded by strong and well-balanced muscles. It is a stable joint with a wide range of motion in many planes. The hip joint, the structural link between the lower extremities and the axial skeleton, not only transmits forces from the ground but also absorbs forces from the trunk, head, neck, and upper extremities. Therefore, the hip joint is one of the most important joints in both daily life activities and sports activities. A good understanding of the hip anatomy and the forces acting on the joint can enhance current and future knowledge. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.